MODERN ASPECTS OF PATIENT ADAPTATION TO REMOVABLE DENTURES (LITERATURE REVIEW) - Salimov Odilxon Rustamovich; Raximov Baxtiyorjon Gafurdjanovich; Kosimov Ahror Abror ugli (Scholar Express Journals, 2022)
One of the key modern orthopaedic dentistry problems related to rehabilitation of patients with complete edentulism is the process of their adaptation to artificial orthopaedic constructions. According to fundamental and modern scientific research, the biological factor, i.e. the complex of all reactions of the organism to the prosthesis including psychological reactions that is individual for each user, is the most important one. Development of new conditioned-reflex connections and formation of cortical inhibition of active stimulus, that a full removable denture is, depends directly on the balance and dynamics of patient’s neural processes despite having several common characteristics including chronometric ones that can be revealed in the majority of patients of this category. This article discusses the processes of adaptation and optimization of orthopedic dental care tactics.
Keywords: Removable dentures; adentia; chewing apparatus; mucous membrane